Aortic Dissection and Thrombosis Diagnosed by Emergency Ultrasound in a Patient with Leg Pain and Paralysis - Ann H. Tsung; Leslie C. Nickels; Giuliano De Portu; Eike F. Flach; Latha Ganti Stead (Case Reports in Vascular Medicine)
The authors present a case of aortic dissection and abdominal aortic aneurysm thrombosis in a 78-year-old male who presented to the emergency department (ED) complaining of lower extremity and paralysis for the past 1.5 hours. The initial vital signs in the ED were as follows: blood pressure (BP) 132/88 mmHg, heart rate (HR) 96, respiratory rate (RR) 14, and an oxygen saturation of 94% at room air. Physical exam was notable for pale and cold left leg. The ED physician was unable to palpate or detect a Doppler signal in the left femoral artery. Bedside ultrasound was performed which showed non-pulsatile left femoral artery and limited flow on color Doppler. Abdominal aortic aneurysm screening ultrasound was performed showing a 4.99 cm infrarenal abdominal aortic aneurysm and an intra-aortic thrombus with an intimal flap. Vascular surgery was promptly contacted and the patient underwent emergent aorto-bi-femoral bypass, bilateral four compartment fasciotomy, right common femoral artery endarterectomy with profundoplasty, and subsequent left leg amputation. Emergency physicians should utilize bedside ultrasound in patients who present with risk factors or threatening signs and symptoms that may suggest aortic dissection or aneurysm. Bedside ultrasound decreases time to definitive treatment and the mortality of the patients.